Educational Attainment and Female Empowerment: A Case Study of Jaunsar Region - Dewangan, Danesh Kumar (Journal of Educational Research and Policies, 2026)
Women empowerment is vital for the overall development of a nation. In tribal regions such as Jaunsar in Uttarakhand, education plays a pivotal role in transforming the status of women. This paper explores the social challenges faced by women in the region, the impact of education in overcoming these barriers, and the role of educational initiatives in enhancing women’s economic, social, and political participation. The study highlights that focused efforts in infrastructure development, awareness, and policy implementation are key to empowering women through education in remote tribal regions. The findings underline the necessity for community involvement, customized educational programs, and government collaboration to bring sustainable development in tribal belts.